CHALLENGES IN INTEGRATING ENGLISH FOR SPECIFIC PURPOSES INTO THE INDONESIAN TEFL CURRICULUM: A LITERATURE STUDY - Nabung, Adrianus; Emilia, Emi; Purnawarman, Pupung (Universitas Muhammadiyah Metro, 2024)
This study examines the challenges of integrating English for Specific Purposes (ESP) into Indonesia's Teaching English as a Foreign Language (TEFL) curriculum. As language teaching evolves, ESP integration addresses learners' professional linguistic needs but faces significant obstacles. Based on a literature study from peer-reviewed journals and academic databases, the analysis identifies key challenges, including teacher qualifications, instructional methods, theoretical frameworks, varied learner proficiency, inadequate materials, institutional policies, and the lack of curriculum guidelines and assessment strategies. The study emphasizes the crucial role of teachers in overcoming these issues, noting a gap between theoretical concepts and practical application in ESP teaching. Addressing these challenges is essential for improving language learning outcomes. The findings highlight the need for teacher professional development and collaborative efforts to establish comprehensive ESP integration frameworks. This study contributes to the discourse on language education in Indonesia, offering insights for future research to enhance teaching practices and outcomes.